Ordering and Production Decisions with Supply Quality and Demand Uncertainty - Bassok, Y.; Akella, R. (Management Science, 1991)
In this paper, we solve a production planning problem that has a direct bearing on the cost to a facility of vendor quality and reliability. This solution is also an important first step in solving the multi-plant coordination problem. We consider a manufacturing facility with one critical raw material, and one or more products whose demand needs to be met. It is assumed that demand for finished goods and the arrival process for raw material are stochastic. We calculate simultaneously the optimal production level, and the raw material order quantity which minimize the total expected cost subject to capacity and release level constraints. The results obtained by our model (the integrated model) show that the production level should be no larger than the production level obtained by solving the traditional (nonintegrated) models, and that major savings are obtained by solving the integrated model. We are also able to characterize and evaluate the cost of reliable supplies of raw material. In addition we solve the above problem in the presence of capacity constraints. A procedure which allocates capacity to different products is presented.